Social Anxiety and its Associated Factors among Secondary School Adolescents of Kathmandu Metropolitan, Nepal - Tamang, Dichhen; Bhandari, Tulsi Ram (Journal of Nepal Health Research Council, 2025)
Background: Social anxiety is an intense anxiety or fear of being judged, negatively evaluated, or rejected in a social situation. It often develops in early adolescence, which eventually grows up to adulthood, mostly without being diagnosed. This study assessed the prevalence and factors associated with social anxiety in secondary school adolescents.Methods: School-based cross-sectional study design was performed among secondary school adolescents of 10 schools in Kathmandu Metropolitan, Nepal. A total of 360 samples were obtained through multi-stage random sampling using the lottery method. A self-administered questionnaire was used as a data collection tool which included the Liebowitz social anxiety scale for children and adolescents. Data entry and analysis were done by using Epi Data and Statistical Package for Social Science (SPSS) software. Results: The prevalence of social anxiety was 39.7% which was higher in females. The study found that 33.3% of the participants were in the high-risk category. A strong association (p<.001) was seen between self-perception and social anxiety. Similarly, a significant relationship (p<.001) was found with social experience-related variables, which included: the experience of traumatic situations, and being discriminated against bullied. Conclusions: A high prevalence of social anxiety among adolescents was seen. One-third of the participants were in the high-risk category, clearly stating that the diagnosed cases only represented the tip of the iceberg. School-based youth-friendly entertainment and engagement interventions considering their emotional and mental health, might be beneficial in dealing with it.Keywords: Adolescents; peer victimization; self-perception; social anxiety